1977
DOI: 10.1007/bf01145461
|View full text |Cite
|
Sign up to set email alerts
|

A further look at equilibrium theory: Visual interaction as a function of interpersonal distance

Abstract: This paper presents a study that examined the relationship between visual interaction and interpersonal distance as it relates to an equilibrium theory of social interaction. Differential boundaries were found to exist for the effect of distance on five highly related male and female visual behaviors, exemplifying different overall equilibrium levels for the sexes. While males looked more as dis tance increased, females looked less after an intermediate distance of 6.5 feet. These data support a modified equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 22 publications
(25 reference statements)
5
29
0
1
Order By: Relevance
“…Specifically, men maintain less personal space between themselves and other people than women do (Aiello, 1977), and the characteristics of the people men are interacting with have a greater influence on the amount of personal space men will allow their counterparts than on the amount of personal space women will allow (Pedersen & Heaston, 1972). It could be that this sex difference will be reflected in proximity and joint contact with a novel toy when an adult demonstrates the toy to a child.…”
Section: Fathers' Role In Infants' Developmentmentioning
confidence: 91%
“…Specifically, men maintain less personal space between themselves and other people than women do (Aiello, 1977), and the characteristics of the people men are interacting with have a greater influence on the amount of personal space men will allow their counterparts than on the amount of personal space women will allow (Pedersen & Heaston, 1972). It could be that this sex difference will be reflected in proximity and joint contact with a novel toy when an adult demonstrates the toy to a child.…”
Section: Fathers' Role In Infants' Developmentmentioning
confidence: 91%
“…The effect of gender composition was significant, F [2,827] The effect of the covariate talk sum was also significant, F[2,827] ϭ 8.50, p ϭ 0.004, 2 ϭ 0.01. The correlation coefficient between talk sum and gaze sum was Ϫ0.08 (p ϭ 0.007).…”
Section: Mutual Gazementioning
confidence: 99%
“…Given that men tend to have a more independent self-construal and women a more interdependent self-construal, it is not surprising to find that women often prefer closer interaction distance than men (Aiello, 1977;Camperio & Malaman, 2002) and react more positively to others within close physical proximity (Hai, Khairullah, & Coulmas, 1982;Ross, Layton, Erickson, & Schopler, 1973). 2 It follows that even though decreased interpersonal distance can induce higher levels of arousal among both men and women, they may label the same arousal state differently.…”
Section: Sex Differences In Reactions To Physical Closenessmentioning
confidence: 95%
“…An accumulation of evidence suggests that people react 2 Even though women are more accustomed to intimacy with another woman than with another man, whereas men's demand for distance is more pronounced in interaction with another man than with another woman (Leibman, 1970), this does not necessarily challenge the notion that women in general prefer closer interaction distance than men. Indeed, studies have found that women in general are more comfortable at closer interaction distance than men regardless of the sex of the person with whom they interact (Aiello, 1977;Camperio & Malaman, 2002). to a person on the screen similarly to an actual person.…”
Section: The Effect Of Facial Close-ups and Viewers' Sex On Empathymentioning
confidence: 97%